Antimalarial Activity (Plasmodium falciparum 3D7) from Sea Sponge Acanthella sp. - faidzil Ikram; Asep Awaludin Prihanto; Choiriyatun Hanifah; Muhammad Iqbal (Natural B, Journal of Health and Environmental Sciences, 2012)
The objective of the research was to get the bioactive candidates from marine sponge Acanthella sp. for anti multi resistant malaria. The first Research was conducted with isolating the active compounds of Acanthella sp. In vitro antimalarial test against Plasmodium falciparum 3D7 was done with several concentrations with positive control using chloroquinon the quantification of the Scizon inhibition was performed with blood staining. Afterward, the infected erythrocytes per 1000 erythrocytes was calculated. IC50 was assayed with probit analysis. The result indicated that all four active fractions showed inhibition on growth of P. Falciparum with different value on IC50. The best fraction is confirmed by fraction B with IC50 of 0.013 ppm.